2015
DOI: 10.1108/sc-05-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Policing “uncontrollable banshees”: factors influencing arrest decision making

Abstract: Purpose – The purpose of this paper is to examine the factors that influence police officers’ decision making when dealing with young women considered violent. Design/methodology/approach – Semi-structured interviews were carried out with frontline police officers in Scotland on their experiences of responding to incidents where young women displayed violence. Findings – The polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly, citizen age was not part of the data collected and was not included in our analyses. Prior research has demonstrated the salience of these variables to police decision-making, especially when coupled with citizen race (Alpert et al 2007; Smith et al 2006; Tillyer and Engel 2013; Young 2015). In particular, young, minority males often receive harsher outcomes than older, nonminority individuals (Rosenfeld et al 2012; Schafer et al 2006; but see Lytle 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, citizen age was not part of the data collected and was not included in our analyses. Prior research has demonstrated the salience of these variables to police decision-making, especially when coupled with citizen race (Alpert et al 2007; Smith et al 2006; Tillyer and Engel 2013; Young 2015). In particular, young, minority males often receive harsher outcomes than older, nonminority individuals (Rosenfeld et al 2012; Schafer et al 2006; but see Lytle 2014).…”
Section: Discussionmentioning
confidence: 99%